PENGARUH PERHATIAN ORANG TUA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK SEKOLAH DASAR - Deviyanti Pangestu; Erni Mustakim; Rizky Putriyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The problem in this study is the low learning motivation of the fifth grade students of State Elementary School 2 Campang Raya in the 2021/2022 academic year. The purpose of this study was to examine the significant effect of parental attention on the learning motivation of fifth grade students. This study used an ex-post facto method with quantitative research. A sample of 69 students is taken using a probability sampling teachnique, namely proportionate stratified random sampling. Data collection techniques in the from of questionnaires and document studies. The istrument has previously been tested for validity an reliability. The data analysis technique used a simple linier regression test. The results showed that there was a significant effect of parental attention on the learning motivation of fifth grade students at State Elementary School 2 Campang Raya in the 2021/2022 academic year.